2022
DOI: 10.1111/1759-7714.14433
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in neoadjuvant versus adjuvant therapy of esophageal cancer treatment trial (QUINTETT): Randomized parallel clinical superiority trial

Abstract: The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. There are no other potential conflicts of interest relevant to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Ninety-six patients were randomized in QUINTETT, 47 patients to Neoadjuvant arm and 49 patients to Adjuvant arm. Patient characteristics are summarized and results from QUINTETT based on all 96 enrolled patients have been reported previously [22]. For the secondary correlative analysis of CTCs, 74 (77.1%) patients had CTC data available and were included in this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety-six patients were randomized in QUINTETT, 47 patients to Neoadjuvant arm and 49 patients to Adjuvant arm. Patient characteristics are summarized and results from QUINTETT based on all 96 enrolled patients have been reported previously [22]. For the secondary correlative analysis of CTCs, 74 (77.1%) patients had CTC data available and were included in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Per QUINTETT trial [22] patients were stratified by clinical nodal status (N0 vs. N1) and by surgeon and then randomized 1:1 to either Neoadjuvant treatment arm (control) or Adjuvant treatment arm (intervention). Randomization occurred centrally through the…”
Section: Randomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with national and international clinical guidelines, neoadjuvant chemoradiotherapy (nCRT) is recommended as an option to improve treatment outcomes of thoracic esophageal squamous cell carcinoma (TESCC). As this modality improves survival, it has been reviewed in many recently published papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neoadjuvant CRT is expected to be a more or less aggressive regimen. Many authors reported different types and grades of toxicity [4,6,8]. Moreover, some tumors progress during neoadjuvant treatment.…”
Section: Introductionmentioning
confidence: 99%